2019
DOI: 10.1111/wvn.12377
|View full text |Cite
|
Sign up to set email alerts
|

Endorsement and Validation of the Essential Evidence‐Based Practice Competencies for Practicing Nurses in Finland: An Argument Delphi Study

Abstract: Objectives: To explore nurses' views and establish consensus on the key content of the essential evidence-based practice (EBP) competencies developed by Melnyk et al. (2014, Worldviews on Evidence-Based Nursing, 11, 5) for practicing registered nurses (RNs) and advanced practice nurses (APNs) among Finnish nurse panelists.Background: Broad-based integration of best evidence into daily practice is central to effectively improving care quality and patient outcomes. EBP competencies allow healthcare professiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…A set of clear EBP competency for both practicing registered nurses and advanced practice nurses in clinical settings was developed by several nursing leaders. 5,12 Moreover, nurses from the United States reported that they were not yet competent in meeting EBP competency, and the nurse's age, EBP beliefs, EBP mentorship, EBP knowledge, and EBP culture were affecting factors of EBP competency. 13 Although there is an increasing trend on studies' focus on EBP competency among nurses, it calls for more studies to illuminate the status and influence factors of EBP in different countries and regions.…”
Section: Inquirymentioning
confidence: 99%
“…A set of clear EBP competency for both practicing registered nurses and advanced practice nurses in clinical settings was developed by several nursing leaders. 5,12 Moreover, nurses from the United States reported that they were not yet competent in meeting EBP competency, and the nurse's age, EBP beliefs, EBP mentorship, EBP knowledge, and EBP culture were affecting factors of EBP competency. 13 Although there is an increasing trend on studies' focus on EBP competency among nurses, it calls for more studies to illuminate the status and influence factors of EBP in different countries and regions.…”
Section: Inquirymentioning
confidence: 99%
“…A thorough integration of the best scientific evidence into daily practice is key to effective improvements in quality of care and patient outcomes (Saunders, Gallagher-Ford, & Vehviläinen-Julkunen, 2019). The World Health Organization (World Health Organization, 2017), therefore, states that it is imperative for countries in the WHO European region to consider the benefits of evidence-based practice (EBP) and to focus on continuous improvements in quality of care.…”
Section: Introductionmentioning
confidence: 99%
“…Expectations of improvement in EBP quality generate new professional competencies that allow healthcare professionals and organizations to clarify performance expectations regarding EBP and succinctly outline the expected competencies for successful application of best evidence to daily care (Saunders et al, 2019). As the education of nurses has developed from hospital-based training to a competence-based curriculum, set core competencies have become crucial for effective nursing training (Reeves, Fox, & Hodges, 2009).…”
mentioning
confidence: 99%
“…Melnyk, Gallagher-Ford, Long, and Fineout-Overholt (2014) published a set of 13 validated EBP competencies for practicing registered nurses and an additional 11 for advanced practice nurses. These same EBP competencies have also been recently validated in Finland (Saunders, Gallagher-Ford, & Vehviläinen-Julkunen, 2019). While these validated EBP competencies exist, there is limited evidence about their use in education or practice.…”
Section: Introductionmentioning
confidence: 99%